Jewish messianism culminating in the rise and dissemination of Sabbatianism - an excursion into messianic Kabbalah and its theological enterprises - Human, Dirk J. (University of Pretoria, 2023)
Dissertation (MTh (Old Testament Studies))--University of Pretoria, 2022.